An efficient poly(amic acid) salt-stabilised palladium nanocatalyst with excellent recyclable performance for Suzuki–Miyaura coupling reactions under mild conditions. Issue 1 (1st January 2018) - Jin, Xin; Li, Jun; Li, Hengfeng
ABSTRACT: Highly dispersed poly(amic acid) salt-stabilised palladium nanoparticles(PdNPs/PAAS) were synthesised via a facile reduction strategy in aqueous media at room temperature and characterised by transmission electron microscopy, powder X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy and inductively coupled plasma optical emission spectrometer. The nanoparticles were used as catalyst for Suzuki–Miyaura coupling reaction to synthesise biphenyl compounds in short reaction time and high yields under mild conditions, benefiting from highly efficient quasi-homogeneous catalytic activity. The catalyst could be recycled 5 times without obvious loss attributing to the pH response of the PAAS.